PERAN KEAMANAN TRANSAKSI KEUANGAN BERBASIS KOMPUTER TERHADAP PENINGKATAN KINERJA UMKM - Nurafni Oktaviyah; Zulfaidah (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2023)
The purpose of this paper is to determine the role of computer-based financial transaction security on MSME performance. This research is a qualitative research with a literature study approach. This approach focuses on collecting, selecting, and interpreting existing literature, such as books, scientific journals, reports, and other sources of information. The data source used in this study is secondary data. The data collection technique used is documentation originating from textbooks, journals, scientific articles, literature reviews which contain the concepts studied. The data analysis techniques used were (1) formulating research questions, (2) identifying literature sources, (3) selecting and evaluating literature, (4) analyzing literature, (5) interpreting and drawing conclusions, (6) writing and reporting. The results of this study are that the security of computer-based financial transactions has a significant role in improving company performance, both financial performance and non-financial performance. Good financial transaction security is able to prevent fraud, improve services, and strengthen the trust of all parties in MSMEs. Keywords: Financial Transaction, MSMEs, Performance, Security